Stellar spectroscopy methods for study of supernova remnants - Pakhomov, Yu.V.; Chugai, N.N.; Iyudin, A.F. (Advances in Astronomy and Space Physics, 2011)
We present the method for study of the characteristics of the supernova remnants using their absorption properties. The background radiation sources are several stars with wide range of distances. Main task is accurate extraction of stellar spectra from observations. For Vela Jr. supernova remnant we found the absence of typical broad absorption in the spectral lines of Ca ii doublet. Using modeles of supernovae remnants and data on radiation in ⁴⁴Ti γ-ray line we estimated the age and the distance to Vela Jr. We showed that a hypernova may be a probable candidate for Vela Jr. protogenitor.